2019
DOI: 10.1017/ice.2019.45
|View full text |Cite
|
Sign up to set email alerts
|

New SHEA expert guidance for infection prevention in the anesthesia work area needs improvement

Abstract: To the Editor-The recent SHEA Expert Guidance article 1 addresses the following questions: "Should injection ports used by anesthesia providers in the OR be covered with isopropyl alcohol-containing caps? Should injection ports-without alcohol-containing caps-used by anesthesia providers in the OR be scrubbed with alcohol before each use?" SHEA recommends that intravenous "ports may be disinfected either by scrubbing the port with a sterile alcohol-based disinfectant before each use immediately prior to each u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Later studies showed that the main potential infection sources coming from the anaesthesia work area were the hands of the anaesthesia providers (gram negative bacteria, Enterococcus spp) [12][13][14], and the patients skin and hair (S. aureus) [15], and that the pathogens found on the anaesthesia provider's hands can lead to postoperative infections [16].…”
Section: Medical Devicesmentioning
confidence: 99%
“…Later studies showed that the main potential infection sources coming from the anaesthesia work area were the hands of the anaesthesia providers (gram negative bacteria, Enterococcus spp) [12][13][14], and the patients skin and hair (S. aureus) [15], and that the pathogens found on the anaesthesia provider's hands can lead to postoperative infections [16].…”
Section: Medical Devicesmentioning
confidence: 99%